Cerebellar Purkinje Cells and GABA Neurotransmission in the Diabetic Rodent Models: A Systematic Review - Viskasari P Kalanjati; Rayhan B Mahdi; Dwi Martha Nur Aditya (AKSONA, 2025)
Highlight: Reduced cerebellar Purkinje cell numbers and altered dendritic trees due to cell deaths were reported in hyperglycemia.  In hyperglycemia, altered GABAergic neurotransmissions are due to lower GABA synthesis and its receptors expression levels in cerebellum. Impaired motor and cognitive functions were observed related to cerebellar Purkinje cell damage in a diabetic rat model.   ABSTRACT Introduction: Hyperglycemia-induced neurotoxicity has been linked to the cerebellum, specifically the impairment of Purkinje cells; its relation to GABA neurotransmission has yet to be cleared. Objective: We conducted an updated review on the mechanism of hyperglycemia-induced impairment of cerebellar Purkinje cells in a rodent diabetic model. Methods: A modified ScR-PRISMA flow diagram was applied as the screening tool. All English-language research articles published between 2014 and 2024 that containing the purposed topics and were indexed in PubMed and Medline were included. These articles were then critically appraised using the JBI checklist to minimize  potential bias. The final inclusion of 8 articles was included for analysis and discussion, together with additional retrieved articles. Results: Hyperglycemic-induced subjects demonstrated a marked reduction in Purkinje and granular cell populations, accompanied by several morphological impairments. Alterations were observed in GABAergic inhibitory neurotransmission, including receptors and GABA synthesis, compared to controls. These findings are consistent with observed deficits in motor coordination and cerebellar function. Conclusion: Hyperglycemia produces adverse effects on the function and survival of Purkinje cells in the cerebellum. Impaired GABAergic neurotransmission might result as parts of oxidative stress and inflammation induced by hyperglycemia in the cerebellar cells. Taken altogether, these results in motor impairment and cognitive dysfunction.